Peta Penggunaan E-Learning Oleh Dosen Fakultas Ekonomi Dan Bisnis Pasca Hibah Spada - Rahayu, Meika Kurnia Puji (Jurnal Manajemen Bisnis, 2018)
This study aims to analyse the use of e-learning among lecturers of the Faculty of Economics and Business, Universitas Muhammadiyah Yogyakarta after the implementation of an online lecture policy and SPADA grants. This research is based on the fact that the use of e-learning by UMY lecturers is not comparable with the investment that has been made. There are still many lecturers who have not been optimal in using e-learning to improve the quality of teaching. The research subjects were lecturers of the Faculty of Economics and Business with a sample of 65 people. Data was collected using documentation techniques and physical artefacts. Data analysis was carried out by qualitative-descriptive method. The results show that there were significant changes in the number of lecturers who have e-learning accounts after the implementation of university policy in term of use of e-learning in teaching and learning. However, this has not been followed by an optimal use of e-learning since most lecturers use e-learning only to upload lecture material in PowerPoint. A few of the respondents used e-learning for online discussions or exams.